Pedestrian safety: a new method to assess pedestrian kinematics - Ptak, Mariusz (Transport, 2019)
The progress in pedestrian safety enhancement is the result of multi-stage work, which is based mainly on the vehicle enhancement and appropriate traffic organization. However, the full separation of vehicle traffic and pedestrians seem to be impossible nowadays. The paper presents a new method for assessing the influence of vehicle structural components on pedestrian kinematics. An integral part of the method is the relationship, named as the k parameter, which can determinate the geometric property of the pedestrian body movement (kinematics) after a collision. The development of the new algorithm is the answer to the problem of assessing the risk posed by the impact of the vehicle with a high bumper/bonnet reference line (e.g. a Sport Utility Vehicle – SUV) on a pedestrian. The presented method can be a useful engineering tool to assess the safety of vehicles, both brand-new and used. The developed test system binds together a new defined kinematic criterion as well as the existing biomechanical criteria (the assessment of vehicles using pedestrian impactors). The presented method was verified on a compact vehicle and a SUV.